Personality trait theory and multitasking performance: implications for ergonomic design. - Guastello, Andrea D.; Guastello, Stephen J.; Guastello, Denise D. (Theoretical Issues in Ergonomics Science, 2014)
Although system designers usually minimise the role of individual differences in operation, personality variables could explain differences in multitasking performance. A concomitant theoretical issue is whether primary or surface personality traits do a better job of predicting performance than the Five-Factor Model (FFM) or global traits. A sample of 174 undergraduates completed the Sixteen Personality Factor Questionnaire (16PF), which was followed by a performance task. A computer-based task that measured simultaneous performance on an arithmetic task and a mental rotation task was used to measure multitasking performance; scores measured the percent accuracy. Primary traits for low emotional sensitivity and high abstractedness, self-control, and general reasoning were all correlated with performance (R2= .11), but global or traits corresponding to the FFM were not, except in one sporadic task trial. There was also a strong gender effect on performance. Implications for the study of personality traits in ergonomics are discussed.